Review of Automation and Energy Monitoring System for Air-Conditioning and Mechanical Ventilation (ACMV) in Building Malaysia - Abdullah, Muhammad Adib Afham; Razali, Mohd Azahari; Abd Rahman, Ramhuzaini; Ishak, Maizul; Md Som, Mohamad; Yusop, Azli; Mohd Amin, Makeen; Abdul Hadi, Norhadiman (Journal of Advanced Mechanical Engineering Applications, 2022)
Buildings and their components such as ventilation, air conditioning (VAC), and lighting account for most of the energy use in Malaysia. The control system of a building reduces energy usage based on numerous criteria such as luminance or daylight and occupancy by reducing the running duration of the VAC and lamp. As a result, the need for further energy-efficient buildings should be emphasized, given the country's high energy consumption, which puts it at risk of global warming. Energy demand considerably exceeds supply, prompting the installation of increasingly rigorous energy saving measures. Thus, this study conducts a literature analysis on Building Management Systems (BMS) with the goal of integrating building automation systems into new buildings and retrofitting older buildings to make them automation ready. The focus of the building automation market is on increasing user comfort while cutting running expenses. Examining the role of BMSs in improving the energy use of a building's electromechanical systems and emphasizing their superior cost-cutting capabilities in both operations and maintenance would inspire stakeholders and facility owners to embrace automation (residential, commercial, and industrial). The current concept may be incorporated into a single platform for monitoring and controlling multiple pieces of equipment in the future.